Assessment of the Institute for Research Design in Librarianship (IRDL): Impact on the Research Productivity and Careers of Academic Librarians - Albarillo, Frans; Kennedy, Marie R.; Brancolini, Kristine R. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – This article reports the survey findings from a mixed-methods assessment of the six-year Institute for Research Design in Librarianship (IRDL). The Institute for Museum and Library Services (IMLS) provided funding for IRDL from 2014-2019; during this time, 124 academic and research librarians participated in a year-long continuing education program for novice researchers. This article assesses the effectiveness of IRDL in meeting short-term and long-term goals related to research productivity, job performance, and identity as a researcher. Beyond the assessment of IRDL itself, the study addresses the implications of IRDL for creating effective research continuing education programs and institutional support for librarian research.Methods – In the first part of a two-phase study, we surveyed all 124 librarians who completed the in-person summer research workshop and year-long online follow-up program. The lead researcher invited those who completed the survey to participate in the study's second phase, a focus group or an in-depth interview.Results – Eighty-nine participants responded to the survey, for a 72% response rate. The results show that IRDL was successful in helping a majority of participants complete their IRDL project and conduct new research. Participants reported work-related benefits of participating in the program, including tenure, rank promotion, merit-based salary increases, and new employment opportunities. IRDL contributed to developing personal learning networks, research collaborations, and a sense of identity as a researcher. IRDL increased the research confidence of the participants by providing them with research methods instruction, coupled with an opportunity to practice what they have learned during a year-long support program.Conclusion – This assessment study confirms that IRDL is an effective program for novice librarian-researchers who want to improve their research skills, develop new research relationships among their peers, and advance in their careers. It also provides insight into the conditions for a successful continuing education and research support program. Many librarians experience anxiety about conducting and disseminating their research; IRDL demonstrates the importance of placing novice researchers in a supportive environment, where research is viewed as a positive experience that is directly related to professional success. These experiences lead to increased confidence and identity as a researcher, which contributes to increased research productivity.